From structure topology to chemical composition. XII.Titanium silicates : the crystal chemistry of rinkite, Na2Ca4REETi(Si2O7)2OF3 - F. Cámara; E. Sokolova; F. C. Hawthorne (Mineralogical Magazine, 2011)
Rinkite, ideally Na 2Ca 4 REETi(Si 2O 7) 2OF 3, is a common mineral in alkaline andperalkaline rocks. The crystal structures of five rinkite crystals from three alkaline massifs: Ilimaussaq, Greenland; Khibiny, Kola Peninsula, Russia andMont Saint-Hilaire, Canada, have been refinedas two components related by the TWIN matrix (-1 0 0, 0-1 0, 1 0 1) (Mo-Kα radiation). The crystals, a = 7.4132-7.4414, b = 5.6595-5.6816, c = 18.8181-18.9431 Å, β = 101.353-101.424(2)°, V = 776.1-786.7 Å 3, space group P2 1/c, Z = 2, D calc = 3.376-3.502 g cm 3, were analysedusing an electron microprobe subsequent to collection of the X-ray intensity data. Transmission electron microscopy confirmed the presence of pseudomerohedral twinning in rinkite crystals. The crystal structure of rinkite is a framework of TS (titanium silicate) blocks. The TS block consists of HOH sheets (H-heteropolyhedral, O-octahedral). The TS block in rinkite exhibits linkage andstereochemistry typical for Group I (Ti = 1 a.p.f.u.) of Ti disilicate minerals: two H sheets connect to the O sheet such that two (Si 2O 7) groups link to the trans edges of a Na polyhedron of the O sheet. The crystal chemistry of rinkite and nacareniobsite-(Ce) is discussed.